Pengembangan Komunikasi Pembelajaran dalam Penguatan Pendidikan Berbasis Tauhid : Indonesia - Afifi, Subhan; Wijaya, Hariz Enggar (UII, 2025)
This article describes a community service initiative aimed at developing learning communication competencies for early childhood and elementary school teachers in the context of strengthening tauhid-based education. The partners in this community service are Raudhatul Athfal (RA) and Sekolah Dasar Islam Terpadu (SDIT) Darussalam Selokerto, which operate under the auspices of the Darussalam Selokerto Foundation. RA and SDIT Darussalam Selokerto have a vision to educate a generation that is monotheistic, intelligent, and morally upright. Since their establishment, these schools have emphasized the importance of Islamic values education and the integration of these values into both religious and general subjects. However, there is a need for further development of teachers' communication competencies and a deeper understanding of the tauhid-based education concept. Based on the analysis of the partners' problems and needs, this community service activity was designed using a participatory empowerment method, consisting of a series of workshops and mentoring sessions with the following sub-themes: (1) The Urgency of Tauhid-Based Education and Exploration of Teachers' Perceptions, (2) The Concept of Tauhid-Based Education, (3) Learning Communication in Tauhid-Based Education, (4) Integration of Tauhid into the School Curriculum, (5) The Role of Teachers in Tauhid-Based Education, and (6) The Tauhid Curriculum for Educators. Post-activity evaluations indicated that participants perceived the program to have a positive impact on their knowledge and understanding of learning communication and the implementation of tauhid-based education.